ECO-BASED REASONED ACTION MODEL: THE ROLE OF MANAGEMENT CONTROL SYSTEM - Sisdyani, Eka Ardhani (Indonesian Journal of Accounting and Governance, 2020)
This paper aims to enrich Fishbein and Azjen’s Theory of Reasoned Action in predicting theemergence of green behavior by adding institutional-based control system to maintain greenintention’s stability. Intention’s stability is a crucial construct in realizing green behavior, though, itis affected by several instances such as: resources availability, individual capabilities, newinformation, and cooperation and commitment of individuals. For that reason, it is plausible to arguethat the existence of institutional-based control directing green behavior, such as eco-basedmanagement control systems, namely levers of eco-control, can maintain and augment one’s intentionto pursue green behavior. Thus, the paper contributes in enriching the knowledge of the emergenceand persistence of green behavior in organizations.